1968
DOI: 10.1002/anie.196800141
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism and Optical Rotatory Dispersion — Principles and Application to the Investigation of the Stereochemistry of Natural Products

Abstract: According to Table 3, the olefination of aldehydes via phosphorylids also gives good results; however, this method is totally unsuccessful with ketones. This is where the new directed aldol condensation becomes really valuable.It would be interesting in this connection to of the invesfigations.(CGH&P-=CH-CH=NR, like the metalated Schiff's bases, react with ketones in the desired manner. The princ@les of circular dichroism and of oprical rotatory dispersion are described. Examples are given to illustrate the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…On the assumption that the Cotton effect originated from the torsion of the -C=C-C=O moiety, the Cotton effect indicated the left-handed chirality of the conjugated carbonyl moiety (Fig. 4); thus, the configuration of the C-5' was deduced 15 to be R (Beecham, 1972;Snatzke, 1968). Based on these results, the structure of 1 is shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…On the assumption that the Cotton effect originated from the torsion of the -C=C-C=O moiety, the Cotton effect indicated the left-handed chirality of the conjugated carbonyl moiety (Fig. 4); thus, the configuration of the C-5' was deduced 15 to be R (Beecham, 1972;Snatzke, 1968). Based on these results, the structure of 1 is shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…A CH 2 Cl 2 -soluble fraction of the MeOH extract of the stems of C. cascarilloides was separated by various kinds of chromatography to give six new crotofolane diterpenoids, named crotocascarins L-Q (1-6), and a diterpenoid with a new scaffold, named neocrotocascarin (7).…”
Section: Resultsmentioning
confidence: 99%
“…NMR spectral evidence indicated that compound 4 is the g-lactone diastereoisomer of pectinolide B (2). The characteristic resonance for the carbonyl group C-2 (d = 172.5) as well as the vicinal coupling constant ( [5] and circular dichroism [6] curves (De 223 : ±18) was correlated with an (S) configuration at C-5. Mosher ester derivatives used with pectinolide B (2) ( Table 2) corroborated the C-3¢-(S) absolute stereochemistry for compounds 1 ± 3.…”
mentioning
confidence: 92%